2014
DOI: 10.2514/1.j052818
|View full text |Cite
|
Sign up to set email alerts
|

In-Flight Investigation of Transition Under Turbulent Conditions on a Laminar Wing Glove

Abstract: Flight experiments carried out with a motorized glider yield insights into the aerodynamic processes acting on a laminar wing section under varying on-coming flow conditions. Measurement data are obtained on a laminar wing glove equipped with pressure transducers and wall microphones to detect transition and investigate the boundarylayer instabilities. The on-coming flow, including the instantaneous angle of attack and the turbulence characteristics, is measured with hot-wire sensors. The flight tests were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The leading edge, the thickness and the camber of the original airfoil have been modified as described in [1] to compensate for the additional weight and drag due to the glove (airfoil geometry parameters can be found in [2]). Previous investigations showed that the cross-flow velocity on the center section of the glove is less than 2% of the freestream [1] and that the flow can be considered two-dimensional [15]. The laminar-turbulent transition process taking place along the pressure side of the airfoil is investigated with a streamwise array of 20 electret microphones (Sennheiser KE 4-211-2) mounted behind holes of 0.3 mm diameter.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The leading edge, the thickness and the camber of the original airfoil have been modified as described in [1] to compensate for the additional weight and drag due to the glove (airfoil geometry parameters can be found in [2]). Previous investigations showed that the cross-flow velocity on the center section of the glove is less than 2% of the freestream [1] and that the flow can be considered two-dimensional [15]. The laminar-turbulent transition process taking place along the pressure side of the airfoil is investigated with a streamwise array of 20 electret microphones (Sennheiser KE 4-211-2) mounted behind holes of 0.3 mm diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Note that after the measuring bridge circuits, a low-pass filter with a bandwidth of 3.8 kHz is applied to the signals, which limits the upper range of frequencies detected. The X-wire probe is calibrated using the effective angle calibration introduced in [35] and described in detail in [15]. The anemometer outputs are not corrected for temperature changes with respect to the calibration conditions on the ground (temperature difference of around 10 to 20 • C), as none of the analytical correction formulas tested were able to provide satisfying precision [15].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations